The Influence of Price Promotion and Discounts on Sales: Study at A Medical Device Company in Medan City - Rifqah Harahap; Anita Situmorang (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aimed to determine the effect of promotions and price discounts on sales. This research uses quantitative methods. The population in this study is all consumers at a medical device company in Medan City from April to June 2020, totaling 355 buyers. The research sample is 100 consumers, and the determination technique uses random sampling. Data collection methods in this study used observation, interviews, questionnaires, and documentation. The data analysis method used in this study is multiple linear regression analysis. The results showed that partial promotions and price discounts positively and significantly affected sales. Simultaneously promotions and price discounts have a positive and significant effect on sales. In testing the adjusted R square coefficient of determination of 90.4%, the variable promotions and price discounts affect sales.